A FOUNDATION FOR A CULTURE OF JUSTPEACE: Church as a Hermeneutic Community to Promote Peace Narratives - August Cornelis Tamawiwy (Scriptura Indonesia, 2021)
This article argues that a culture of justpeace could be reached if the church as a hermeneutic community interprets all narratives in the light of promoting justpeace. Promoting good narratives will shape us to be peacemakers. By using the concept of Appreciative Inquiry (AI) as a method, this article aims to invite people to engage conflict in a constructive way. This article aims discovers the role of justice, truth, and ecumenical-interreligious dialogue which play in the vision of a culture of justpeace. It also shows how the use of imagination is important in dreaming of a culture of justpeace. It invites us to see how narratives drive our imagination and design our character to make peace or violence.